2015
DOI: 10.1016/j.placenta.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin inhibits expression of sFLT1 from human cytotrophoblasts induced by hypoxia, via cyclo-oxygenase 1

Abstract: Introduction Elevated circulating soluble FLT1 (sFLT1) levels in preeclampsia may play a role in its development. Aspirin is recommended for prevention of preeclampsia. We hypothesized that aspirin may inhibit the production of sFlt1. Methods Placentas from women with and without preeclampsia were collected. Primary cytotrophoblasts (CTBs) were cultured from normal placentas and treated with aspirin, sc-560, a COX1 inhibitor or celecoxib, a COX-2 inhibitor. The expression of sFLT1, FLT1, COX1, COX2 was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 53 publications
0
45
0
4
Order By: Relevance
“…31-33, 36 Aspirin, recommended for SLE pregnancies and studied in PE prevention trials, may decrease sFlt1 production by trophoblasts. 34, 37, 38 Importantly, neither heparin nor aspirin exposure limited the strong prognostic value of angiogenic factors in predicting severe APO in this study.…”
Section: Commentmentioning
confidence: 61%
See 1 more Smart Citation
“…31-33, 36 Aspirin, recommended for SLE pregnancies and studied in PE prevention trials, may decrease sFlt1 production by trophoblasts. 34, 37, 38 Importantly, neither heparin nor aspirin exposure limited the strong prognostic value of angiogenic factors in predicting severe APO in this study.…”
Section: Commentmentioning
confidence: 61%
“…Heparin and low dose aspirin are standard treatments for pregnant women with antiphospholipid syndrome (APS), aspirin alone for those with only APL 31 ; both may alter angiogenic factor levels. 32-34 Patients receiving heparin had significantly higher sFlt1 levels, sFlt1/PlGF ratios, and lower PlGF levels at 12-15 weeks, compared to untreated women; sEng levels were not significantly different between these groups (Table B). Treatment with heparin was associated with a higher risk of severe APO in bivariate analyses but not after adjusting for other covariates.…”
Section: Resultsmentioning
confidence: 94%
“…If replicated in longitudinal studies, these data may provide a basis for targeted interventions to prevent long-term complication of schizophrenia. Current therapeutic avenues that decrease the expression of sFlt-1 [antipsychotics (Buckley et al , 2007), sulfasalazine (Brownfoot et al , 2015b), aspirin (Li et al , 2015), statins (Brownfoot et al , 2015a), proton pump inhibitors (Onda et al , 2015), and choline (Jiang et al , 2013)] and modulate autoimmune disorders are already in existence.…”
Section: Discussionmentioning
confidence: 99%
“…(94,95) However, in an in vivo study, aspirin has been shown to inhibit the expression of soluble fms-like tyrosine kinase (sFlt-1) in cytotrophoblast cultured cells, under a hypoxic state, from placentas of women with confirmed preeclampsia. (96) The result of the current meta-analysis indicates that the administration of low-dose aspirin at <11 weeks' gestation is associated with a nonsignificant decrease in the risk of preeclampsia, gestational hypertension, and any hypertensive disorder of pregnancy. However, when Kaandorp et al 's study (56) is excluded, the effect of aspirin on the rate of any hypertensive disorder of pregnancy becomes significant (Table 3).…”
Section: Resultsmentioning
confidence: 82%